Work place violence among health-care providers working in a tertiary care hospital: A study from Central India - Ashish Mishra; Sunita Patel; Arindam Maiti; Arvind Sharma (Asian Journal of Medical Sciences, 2024)
Background: Health-care providers are prone to either physical, verbal, or both type of violence either by patients or their relatives with majority studies conducted in developed countries with paucity in developing countries like India. Aims and Objectives: This study was conducted to estimate the prevalence of different types of work-place violence and to assess the various factors associated with it among the health-care providers. Materials and Methods: It was a cross-sectional study conducted among total of 253 health-care providers, consisting of both Senior and Junior Residents and Nursing staffs for a period of 6 months. Data were collected, and then entered in MS-Excel with both descriptive and statistical analysis done using IBM-SPSS v23.0. Results: It was observed that 89.72% of the health-care providers experienced violence, where 66.01% of them experienced verbal type, while 23.71% of them experienced both, that is, verbal and physical. It was noted that majority of the health-care providers experienced verbal form of violence due to excessive crowd of attendant, that is, 123 (73.65%). Other factors such as not attending patient for a long time and lacunae of empathy towards patient/attendant have strong association with significant result for violence toward health-care providers, adjusted odds ratio (aOR) =4.69 (2.06–10.66), P=0.001 and aOR=4.52 (1.23–16.65), P=0.014, respectively. Conclusion: This study of workplace violence among health-care providers revealed that majority, that is, nursing staffs experienced verbal violence because they deal with patients and their attenders for maximum time in a day during their duty hours and also due to less experience.